Clinical effectiveness of liraglutide vs basal insulin in a real‐world setting: Evidence of improved glycaemic and weight control in obese people with type 2 diabetes. Issue 9 (29th May 2018) - Overbeek, Jetty A.; Heintjes, Edith M.; Huisman, Eline L.; Tikkanen, Christian K.; van Diermen, Arnout W.; Penning‐van Beest, Fernie J.A.; Herings, Ron M.C.
Abstract : Aims: To compare real‐world antidiabetic treatment outcomes over 12 months in obese people with type 2 diabetes mellitus (T2DM) who previously received oral antidiabetic therapy and then initiated a first injectable therapy with liraglutide or basal insulin. Patients and methods: This was a retrospective, propensity score‐matched, longitudinal cohort study using real‐world data (January 2010 to December 2015) from the Dutch PHARMO Database Network. Adult obese (body mass index [BMI] ≥35 kg/m 2 ) patients with T2DM with ≥2 dispensing dates for liraglutide or basal insulin supported oral therapy (BOT) were selected. The primary endpoint was the change in glycated haemoglobin (HbA1c) from baseline during 12 months of follow‐up. The secondary endpoints were the changes in weight, BMI and cardiovascular risk factors from baseline. Clinical data were analysed using descriptive statistics and compared using mixed models for repeated measures. Results: Obese patients with T2DM ( N = 1157) in each treatment group were matched (liraglutide cohort, n = 544; BOT cohort, n = 613). From 3 months onwards, glycaemic control improved in both cohorts but improved significantly more with liraglutide than with BOT (12 months: −12.2 mmol/mol vs −8.8 mmol/mol; P = .0053). In addition, weight and BMI were significantly lower for treatments with liraglutide vs BOT (12 months: −6.0 kg vs −1.6 kg and − 2.1 kg/m 2 vs −0.5 kg/m 2, respectively; P < .0001 for both). No significant differences were seen in changes in cardiovascular risk factors. Conclusions: The results of this real‐world study in matched obese patients with T2DM showed that liraglutide was more effective than BOT for HbA1c control and weight/BMI reductions. Patients were more likely to maintain glycaemic control over time after initiating liraglutide than after initiating BOT.